ASIA TECHNO FARM - M Rondhi; Nobutaka Ito (UNEJ e-Proceeding, 2017)
Prior to ASEAN Economic Community establishment in December 2015, the author proposedone project entitled "Asia Rice Project" at JSAMFE held at Okinawa, Japan in May, 2014. Theproject concept consists mainly of the followings: 1) Asian agriculture overview, 2) How AECshould be promoted, 3) Collaboration between Resource oriented (ASEAN member)andTechnology oriented (ASEAN plus 3 countries, 4) Making Asia a world food pantry, 5) Hightechnology innovation & application and transfer 6) Human resources development based onuniversity consortium and student mobility, 7) Create & develop new Asia brand of foodproducts, 6) Mutual benefit & prosperity for collaboration, 7) Final goal is to achieve the finalgoal of economic promotion and regional peace keeping. In this paper the concrete practicalways how the program should be managed and operated to materialize and promote theprogram of Asia Food Project.